Using Physical Education Courses to Help Increase Well-Being of RN-BSN Nursing Students: An Exploratory Analysis of Outcomes - John E. Lothes II; Debra A. Hrelic; Amy Olsen (The Ohio State University Libraries, 2020)
Background: Student health and wellness has been a growing concern over the years. Evidence is showing that behaviors and health patterns developed in college tend to hold through the years after graduation. Aim: To examine the pre-post wellness outcomes of nursing students taking a physical education course in an online accelerated Registered Nurse-Bachelor of Science Nursing (RN-BSN) program at a university in the Southeast region of the United States. Methods: An online course with incorporated physical activities and tutorials was designed based on the Travis Wellness Inventory to teach about 12 different dimensions of wellness. Students completed modules that addressed different aspects of wellness. Wellness was assessed using the Wellness Inventory and pre-post outcomes were examined.  Results: The results found statistically significant changes between the pre and post assessments for all dimensions of wellness outcomes. There were also significant changes between the pre and post assessments when investigating differences based on gender with females improving on all 12 dimensions and males on 4. Conclusion: Introductory Physical Education (PED101) courses may be useful in improving wellness and reducing stress and turnover for RN-BSN students.